SPECIAL ZONE FOR SHIP WASHING IN TRANSBOUNDARY MARINE POLLUTION REDUCTION AT MALAKA STRAIT - Verdinand Robertua; Bryan Libertho Karyoprawiro; Eunike Meliani Wahyuningtyas (Sociae Polites, 2019)
The Malacca Strait, which has always been the world's most strategic trade route, has become the most frequently traversed by international ships. The potential for environmental pollution in the Malacca Strait is also enormous, especially pollution from ship waste in the form of liquid waste (water ballasts and hazardous toxic materials, or B3 liquid waste) and garbage from disposal during illegal ship washing. Bintan Island, which located close to the Malacca Strait, is one of the islands affected by foreign ship dumping, which avoids sanctions throughout Indonesia, such as Malaysia and Singapore, which require every incoming vessel to be clean of waste. Regulations made by the Singapore government regarding the inspection of the ships of each ship resulted in the act of washing boats in the Malacca Strait. Cleaning and washing tanks and vessels in inappropriate areas can result in environmental pollution caused by wastewater in the form of water, oil, and plastic waste that is very damaging to the environment. The establishment of an exclusive zone for ships carrying out ship cleaning activities as well as anchored anchor locations can reduce environmental damage in the Malacca Strait. This study uses a qualitative method using an ecological approach to see how ecological problems caused by ships cause cross-border issues that threaten ecosystems in the Malacca Strait, specifically the Bintan Islands conservation area. The data used in the form of qualitative data collected through document studies, interviews, document analysis, focused discussions, and observations made.